Trends in the Development of Basic Computer Education at Universities - Dolinsky, Michael (Universitas Ahmad Dahlan, 2023)
Basic computer education in universities is experiencing huge problems. On the one hand, the amount of knowledge that a university graduate must have is increasing very quickly. On the other hand, the contingent of students varies greatly in terms of the level of training and motivation, and the level of this differentiation is constantly growing. As a result, the complexity of training and the percentage of dropouts increase. Scientists and educators are looking for a solution to these problems in the following areas: revising the knowledge necessary for obtaining at the university in the direction of the reality of their receipt in the allotted time; the use of new information technologies to simplify the learning process and improve its quality; development of the latest teaching methods that take into account the realities. This paper presents a strategic document in the field of computer education at universities - Computing Circulum 2020, as well as an overview of the areas of development of basic computer education, such as learning using artificial intelligence, virtual laboratories, microprocessor kits and robotics, WEB - systems for distance and blended learning, mobile application development, visual programming, gamification, computer architecture & organization, programming languages, learning technologies. In addition, the author gives his experience and vision of teaching basic computer education at universities.